Collaborative Performance Metrics Model with Lateral Structure in Fresh Produce Supply Chains: A Review - Novirani, Dwi; Susanto, Edi; Othman, Norfaridatul Akmaliah; Gunawan, Sri (The University of Lampung, 2024)
Performance measurement regarding collaborative supply chain of fresh produces such as fruit and vegetables that combines vertical and horizontal collaboration structures is rarely found in the literature. Performance metrics in this lateral collaborative structure are useful for tracking and measuring the achievement of more comprehensive business goals that are not found in only vertical or horizontal structures. This research aims to explore and propose the best model for collaborative performance system (CPS) in the fresh produce supply chain (FPSC) and success factors in CPS implementation, including CPS metrics and matching collaborative individual performance (CIP) and supply chain performance (SCP). Papers from the last seventeen years including journal papers, working papers and conferences were selected in three steps. From 175 articles found in the first step, 63 articles matched the topic. In the third step, 48 articles were selected as important topics of discussion focused on the field of fresh products, with three classifications of collaboration structures and identifying CIP and SCP metrics which were then analyzed. The results of this review provide good opportunity as reference material for further research, through a comprehensive analytical description complete with a conceptual model presented to complete the gaps in this field. Keywords: Collaborative Performance System, Lateral Model, Performance Metrics, Rural Farmers, Supply Chain.